Penerapan Pendekatan CTL untuk Meningkatkan Hasil Belajar Sifat Bangun Ruang Siswa Kelas V SD - Angraini, Elli; Dalais, Mursal; Ahmad, Syafri (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2018)
The aim of the research is to describe the plan, implementation, and the learning outcome of the “Shape and Space of Geometri” by using Contextual Teaching and Learning Approaches at 5th grade of SDN 24 VII Koto Sungai Sarik Pariaman. The classroom action research was conducted by applying both qualitative and quantitative approaches. Subjects of the research were the teacher and 16 students of the school. The result of the research shows that: (a) the lesson plan 80,35% in the first cycle increased to 91.06% in the second cycle, (b) the teacher’s teaching aspect 78.57% in the first cycle increased to 87.49% in the second cycle  increased, (c) the student’s learning aspect 71.42% in the first cycle increased to 87.49% in the second cycle, (d) the learning outcome 70.70 in the first cycle increased to 88.17 in the second cycle.Keywords: Shape and Space of Geometri, the Contextual Teaching and Learning Approach